EXAMINING CRISIS COMMUNICATION AND ONLINE ACTIVISM IN INDONESIA: A CASE STUDY ON 2022 VOTRE PEAU - Veritasia, Mytha Eliva; Suteja, Rani Sukma Ayu (Laboratorium Ilmu Komunikasi Fisip UHO, 2024)
This article discusses the crisis experienced by a local beauty brand, Votre Peau, in 2022, following an internal event featuring a